CENTRE-STATE RELATIONS, FINANCE COMMISSIONS AND KERALA'S FISCAL CRISIS - K.K.George K.K.Krishnakumar (CSESWP10, 2003)
In the context of the ongoing work of the Twelfth Finance Commission chaired by Dr.C.Rangarajan, this paper examines, the record of the fiscal transfer mechanism in India particularly that of the Finance Commissions. The specific objective of the present enquiry is to find out to what extent the deficiencies of these mechanisms are responsible for accentuating the recurrent fiscal crisis of the States. The issue is examined with particular reference to Kerala. The paper is divided into two sections. Section I takes a look at the past record of vertical transfers viz., transfers from the Centre to the States as a whole. Section II examines the trends in horizontal transfers, viz. interstate distribution of Central transfers. It examines, in particular, the flow of Central government funds to Kerala in comparison with that going to other States. It discusses in detail the different criteria for Central transfers adopted by recent Finance Commissions which led to Kerala receiving lower than All States average quantum of Central funds. It argues in favour of the Twelfth Finance Commission adopting altogether new criteria, taking into account the unique pattern of Kerala's development and the resulting problems which again are unique to the State